Analysis of the Influence of Return On Assets, Return on Equity, Total Assets Turnover, and Inventory Turnover on Profit Growth - Gilang Rawanggin; Adya Hermawati; Alfiana (Journal of Management Research and Studies, 2025)
This study aims to test and analyze the effect of Return On Assets (ROA), Return On Equity (ROE), Total Assets Turnover (TATO), and Inventory Turnover (ITO) on profit growth in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. This industry was chosen because of its strategic role in meeting the basic needs of the community and its high operational activities, thus demanding effective resource management to achieve maximum profits. The research method used is a quantitative approach with secondary data obtained from the company's annual financial statements. The sample was determined with certain criteria to ensure the relevance of the data during the observation period which includes the dynamics of the post-pandemic economy. The main theoretical foundations used are Resource-Based Theory (RBT) which emphasizes the management of internal resources to achieve competitive advantage, and Signaling Theory which places financial ratios as performance signals for external parties. The results of the study are expected to provide empirical evidence on how the efficiency of asset management, equity, and inventory turnover contributes to the increase in the company's net profit. Practically, this research is useful for company management in evaluating operational effectiveness and for investors as a consideration in making investment decisions. These findings also enrich the financial management literature related to the dynamics of profit growth in the consumer goods industry sector in Indonesia.